Sensitivity Analysis of Wastewater Flow Quality in A Channel Under The Influence of Hydraulic Retention Time Variations - Gholipour, Amir; Akbari, Abolghasem (Penerbit UMP, 2015)
Urgent water supply issues coupled with environmental factors have resulted in a greater focus on treating waste water effluent. As technological treatment is costly, the use of naturally-purifying systems is significant. In this study, the sensitive analysis of flow quality under the influence of Hydraulic Retention Time (HRT) variations has been carried out using the numerical model of Q2K. The study is conducted in the proposed 10 km concrete open channel for transmission of sewage from Mashhad city to Parkand-Abad wastewater treatment plant (WWTP), Iran. Results show that after 12 hr from entering flow to the channel, Dissolved Oxygen (DO) concentrations increase with rising HRT along the transmit channel. However, BOD, Organic Nitrogen (NO), Total Coliform (Tcoli), Organic Phosphorous (PO), Particle Organic Matter (POM), Total Suspended Solids (TSS) and Total Organic Carbon (TOC) was reduced by 70%, 35%, 35%, 35%, 80%, 85%, 15%, 10% and 80% respectively. Likewise, when HRT becomes greater; NO3, PH and NH4increased which means greater HRTs in aerobic processes have undesirable influence on NO3 and NH4 indexes concentration. As well, the numerical outcomes are in conformity to experimental data.